On the nature of insight solutions: Evidence from skill differences in anagram solution. - Novick, Laura R.; Sherman, Steven J. (Quarterly Journal of Experimental Psychology: Section A, 2003)
The writers argue that their analysis of pop-out solutions—solutions that come to mind suddenly with no awareness of the process by which they were created—to anagrams has enabled them to link the Gestalt view of insight with considerations of expertise differences in problem solving. They argue that although their findings demonstrated that both pop-out and search solutions to anagrams depend on the gradual accumulation of partial information they nevertheless suggested that there may be some merit to the Gestalt claim that pop-out solutions are qualitatively different from search solutions. They assert that pop-out solutions, which are more frequently obtained by highly skilled solvers, may arise from parallel processing of the constraints on the rearranged order of the anagram letters. Furthermore, they elaborate that there may be a transition from primarily serial to greater parallel processing with increasing expertise in the domain of anagram solution.